Implementasi Metode Six Sigma Untuk Peningkatan Kualitas Air Minum Kemasan - Siswanto; Suling, Moh. Rifandhi; Kayatun, Siti Nur (Metode : Jurnal Teknik Industri, 2025)
PT. Uwe Molino Luwuk is a company engaged in the production of glass bottled drinking water. However, the product often experiences defects such as inappropriate closures, packaging damage that causes leaks, and lack of precision in the cup sealer. This condition causes the product not to meet consumer expectations for quality. This research aims to reduce the level of defects in each production sub-process by determining the initial performance conditions (baseline) and targets to be achieved. Through the application of Six Sigma, it is hoped that it will be able to reduce process variability, so that product quality can be more consistent with decreasing defect rates. The research results show that the DPMO (Defects Per Million Opportunities) value which varies from 33.39 to 1,885.87 shows that there are fluctuations in production quality and based on the Sigma value, most of the production processes are at level 4 to 5 Sigma, which means overall production quality, overall quite good, achieving Sigma 5.48 defect level